Biomass porous carbon electrode material, preparation method thereof and application of biomass porous carbon electrode material in room-temperature sodium-sulfur battery
By using biomass porous carbon electrode materials, the shuttle effect problems caused by limited battery resources and polysulfide conversion are solved, and a high-performance and environmentally friendly room-temperature sodium-sulfur battery electrode material is achieved.
Patent Information
- Application Number
- CN202411544091.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The resources of traditional metal ion batteries are limited, and the shuttle effect caused by the conversion of polysulfides in room temperature sodium-sulfur batteries leads to unstable battery performance.
Using biomass porous carbon electrode material, pretreat biomass waste, add pore-forming agent and activation treatment, form a multi-stage pore structure, and mix it with sulfur powder for heat treatment to prepare electrodes with high specific surface area and stable pore structure. Material.
It improves the rate performance and cycle stability of the battery, reduces the shuttle effect of polysulfides, improves the actual specific capacity and coulomb efficiency, and uses biomass waste to reduce the cost of raw materials, which is in line with environmental protection concepts.
Smart Images

Figure CN119481058A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of positive electrode materials for room temperature sodium-sulfur batteries, and specifically relates to a biomass porous carbon electrode material and a preparation method thereof and application in room temperature sodium-sulfur batteries. Background Art
[0002] Common energy storage systems include battery energy storage systems, supercapacitor energy storage systems, compressed air energy storage systems, water pump energy storage systems and flywheel energy storage systems. Among various energy storage systems, metal ion batteries have become one of the most promising energy storage and conversion technologies. Among metal ion batteries, lithium ion batteries are widely used in people's daily lives due to their high energy density and excellent cycle stability. However, with the in-depth research of researchers and the advancement of the industrialization process of lithium ion batteries in companies, the abundance of lithium resources is in short supply, and finding alternative secondary batteries has become a new development trend.
[0003] Natural biomass materials have undergone millions of years of evolution and present a unique structure. Compared with traditional carbon materials, biomass carbon prepared from biomass materials has a low degree of graphitization and a significantly larger interlayer spacing, which is suitable for sodium ions with a larger ion radius. Introducing pore-forming agents such as potassium hydroxide, potassium citrate, sodium hydroxide, zinc chloride, etc. into biomass carbon materials can significantly improve their morphology and structure, provide a larger interlayer spacing for the embedding of sodium ions, and the multi-level pore structure formed can effectively alleviate the volume expansion of sulfur and control the conversion process of sodium polysulfide, thereby improving the long cycle and rate stability of sodium-sulfur batteries.
[0004] Some researchers have combined metal atoms and carbon materials as positive electrode materials for room temperature sodium-sulfur batteries to catalyze the conversion of polysulfides. However, the synthesis process of metal atoms is complex, costly, and difficult to industrialize. Pure carbon materials cannot withstand the volume expansion in electrochemical reactions. Therefore, it is of great significance to develop a biomass porous carbon electrode material with cheap and easily available raw materials, environmentally friendly, and multi-level pores. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a biomass porous carbon electrode material and a preparation method thereof and an application in a room temperature sodium-sulfur battery, so as to solve the technical problems of the limited resources of traditional metal ion batteries and the shuttle effect caused by the conversion of polysulfides in room temperature sodium-sulfur batteries.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a biomass porous carbon electrode material, comprising: The biomass waste is pretreated to obtain powder A; the powder A is pre-carbonized to obtain powder B; a pore-forming agent is added to the powder B and mixed and ball-milled to obtain powder C; the powder C is activated to obtain powder D; a hydrochloric acid solution is added to the powder D, heated and stirred, and after washing, filtering and drying, a biomass porous carbon material is obtained; the biomass porous carbon material is then mixed with sulfur powder, and after heat treatment, a biomass porous carbon electrode material is obtained.
[0007] Preferably, the biomass waste is corn stalks; the pretreatment conditions are: washing with deionized water and ethanol in sequence and drying and grinding; the drying conditions are drying at 70-90° C. for 12-24 hours.
[0008] Preferably, the pre-carbonization conditions are: in an argon protective atmosphere, heating to 600-1400° C. at a heating rate of 10-30° C. / min, and keeping the temperature for 3-5 hours; the argon flow rate is 60-100 sccm.
[0009] Preferably, the pore-forming agent is potassium hydroxide, potassium citrate, zinc chloride or sodium hydroxide; the mass ratio of powdered B to the pore-forming agent is 1:(1-5); and the ball milling time is 1-3h.
[0010] Preferably, the activation conditions are: in an argon protective atmosphere, heating to 600-1000° C. at a heating rate of 10-30° C. / min, and keeping the temperature for 1-5 hours; the argon flow rate is 60-100 sccm.
[0011] Preferably, 40-90 mL of a hydrochloric acid solution having a concentration of 1-5 mol / L is added to every 1-5 g of powdered D.
[0012] Preferably, the heating and stirring conditions are: heating and stirring at a speed of 300 r / min in a 70-90° C. water bath for 6-12 h; the cleaning conditions are: cleaning with deionized water and ethanol in sequence; and the drying conditions are: drying at 70-90° C. for 24-48 h.
[0013] Preferably, the mass ratio of the biomass porous carbon material to the sulfur powder is (2-5): (5-8); the heat treatment conditions are: heat treatment at 155-180° C. for 12-18 hours.
[0014] The invention also discloses a biomass porous carbon electrode material, which is prepared by the above preparation method.
[0015] The invention also discloses the application of the biomass porous carbon electrode material prepared by the preparation method in a room temperature sodium-sulfur battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a biomass porous carbon electrode material. By using biomass waste as raw materials, not only the effective recycling of resources is achieved, but also the cost of raw materials is reduced and the economic benefits of the process are enhanced. At the same time, the selection of biomass materials conforms to the concept of green environmental protection and reduces the burden on the environment. The pre-carbonization process helps to stabilize the structure of the biomass material, remove volatile components, and lay a good foundation for pore formation and activation in subsequent steps. This process is crucial for forming a stable porous structure and helps to improve the performance of the final electrode material. By adding a pore-forming agent and mixing and ball milling, a multi-level pore structure can be introduced into the material. This structure is very beneficial for the electrode material because it can increase the specific surface area of the material, provide more active sites, and help the penetration of the electrolyte and the transmission of ions, thereby improving the rate performance and actual specific capacity of the battery. The activation step can further optimize the pore structure of the material and increase the porosity and specific surface area of the material. This helps to increase the contact area between the material and the electrolyte, promote the electrochemical reaction, and thus improve the electrochemical performance of the battery. Adding hydrochloric acid solution, heating and stirring are mainly to remove impurities and residual pore-forming agents in the material to ensure the purity of the final product. By washing, filtering and drying, a biomass porous carbon material with excellent pore structure can be obtained, providing a high-quality substrate for subsequent electrode preparation. The biomass porous carbon material is mixed with sulfur powder and heat-treated, and sulfur can be uniformly loaded in the pores of the porous carbon material. This composite structure not only improves the utilization rate of sulfur, but also effectively inhibits the shuttle effect of polysulfides. At the same time, the stability of the porous carbon material also enhances the stability of the electrode material during the electrochemical reaction, thereby improving the rate performance and cycle stability of the battery. The preparation method of the present invention is simple and easy, and the raw materials and reagents used are easy to obtain. The entire preparation process is green and environmentally friendly, and conforms to the concept of sustainable development. This makes the preparation method have good industrial application prospects and can produce high-performance biomass porous carbon electrode materials on a large scale.
[0017] The present invention also discloses a biomass porous carbon electrode material prepared by the above-mentioned preparation method. The multi-level pore structure of the biomass porous carbon electrode material can accommodate more sulfur and alleviate its volume expansion, thereby improving battery performance. The pore structure promotes rapid ion transmission, reduces internal resistance, and increases battery reaction rate. The small pore structure captures polysulfides, reduces their shuttle in the electrolyte, and improves Coulomb efficiency and cycle life. Using biomass waste as raw materials reduces costs and reduces dependence on fossil resources.
[0018] The present invention also discloses the application of the biomass porous carbon electrode material prepared by the above-mentioned preparation method in a room temperature sodium-sulfur battery. The electrode material prepared by the present invention is applied to the room temperature sodium-sulfur battery, not only showing excellent electrochemical performance, but also having good economic benefits and environmental friendliness. Biomass is selected as waste, which is green and environmentally friendly and suitable for industrial application. The room temperature sodium-sulfur battery positive electrode material synthesized by the present invention is activated by chemical reagents, and has a multi-level pore structure and a physical method to inhibit the volume expansion of the positive electrode. The macropores are conducive to the passage of electrolyte ions, the mesopores can ensure a higher sulfur loading, and the small pores can provide an extremely high specific surface area and a large adsorption volume, which can effectively solve the shuttle effect caused by the conversion of polysulfides in the room temperature sodium-sulfur battery, and improve the actual specific capacity and rate performance of the room temperature sodium-sulfur battery. The biomass porous carbon electrode material is applied to the room temperature sodium-sulfur battery to increase the stability during the electrochemical reaction, thereby improving the rate performance of the battery system and ensuring the stability of long cycles at high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the XRD diagram of the biomass porous carbon electrode material prepared in Example 1, Example 2 and Example 3 of the present invention.
[0020] Figure 2 These are SEM images of the biomass porous carbon electrode materials prepared in Examples 1, 2 and 3 of the present invention; wherein, (a) is a 10,000-fold SEM image of Example 1; (b) is a 10,000-fold SEM image of Example 2; (c) is a 10,000-fold SEM image of Example 3; (d) is a 50,000-fold SEM image of Example 1; (e) is a 50,000-fold SEM image of Example 2; and (f) is a 50,000-fold SEM image of Example 3.
[0021] Figure 3 This is a Raman spectrum diagram of the biomass porous carbon electrode material prepared in Example 1, Example 2 and Example 3 of the present invention.
[0022] Figure 4 The biomass porous carbon electrode material prepared in Examples 1, 2 and 3 of the present invention is 5Ag -1 The long cycle performance diagram below.
[0023] Figure 5 This is a rate performance diagram of the biomass porous carbon electrode material prepared in Example 1, Example 2 and Example 3 of the present invention. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention discloses a method for preparing a biomass porous carbon electrode material, comprising the following steps: 1) The biomass waste is washed with deionized water and ethanol in sequence, and then dried and ground to obtain powder A; 2) Pre-carbonize powder A in an argon protective atmosphere at a temperature of 600-1400°C for 3-5 hours, and cool to room temperature to obtain powder B; 3) Add pore-forming agent to powder B and mix, then ball-mill for 1-3 hours to obtain powder C; 4) Activate powdered C in an argon protective atmosphere at a temperature of 600-1000°C for 1-5 hours, and cool to room temperature to obtain powdered D; 5) Adding hydrochloric acid solution to powder D, heating and stirring, washing the obtained product with deionized water and ethanol, filtering, and drying to obtain powder E, that is, obtaining a biomass porous carbon material; 6) The biomass porous carbon material is mixed with sulfur powder and subjected to heat treatment to obtain a biomass porous carbon electrode material.
[0027] Furthermore, in step 1), the biomass waste is corn stalks.
[0028] Furthermore, the drying in step 1) is specifically: drying in an oven at 70-90° C. for 12-24 hours.
[0029] Furthermore, the pre-carbonization in step 2) is specifically as follows: the heating rate is 10-30°C / min, the gas flow rate is 60-100sccm, and the holding time is 3-5h.
[0030] Furthermore, in step 3), the pore-forming agent is potassium hydroxide, potassium citrate, zinc chloride, sodium hydroxide, etc.
[0031] Furthermore, in step 3), the mass ratio of powdered B to pore-forming agent is 1:(1-5).
[0032] Furthermore, the activation in step 4) is specifically as follows: the heating rate is 10-30°C / min, the gas flow rate is 60-100sccm, and the holding time is 1-5h.
[0033] Furthermore, in step 5), 1-5 g of powdered D is added to every 40-90 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 1-5 mol / L.
[0034] Furthermore, the heating and stirring in step 5) is specifically: heating in a water bath at a temperature of 70-90° C., a rotation speed of 300 r / min, and stirring for 6-12 h.
[0035] Furthermore, in step 5), the drying temperature is 70-90° C. and the drying time is 24-48 hours.
[0036] Furthermore, in step 6), the mass ratio of the biomass porous carbon material to the sulfur powder is (2-5): (5-8); preferably, 5:5, 4:6, 3:7, 2:8.
[0037] Furthermore, the heat treatment conditions in step 6) are: heat treatment at 155-180° C. for 12-18 hours.
[0038] The present invention discloses a method for preparing a biomass porous carbon electrode material, which specifically comprises the following steps: 1) The biomass waste corn stalks are cleaned with deionized water and ethanol in sequence, and then dried in an oven at 70-90° C. for 12-24 hours, and then crushed and ground to obtain powder A; 2) Pre-carbonizing powder A at 600-1400°C under argon protective atmosphere, with a heating rate of 10-30°C / min, a gas flow rate of 60-100sccm, a holding time of 3-5h, and cooling to room temperature to obtain powder B; 3) Adding a pore former such as potassium citrate to powder B, the mass ratio of powder B to pore former is 1:1, 1:2, 1:3, 1:4, 1:5, mixing and then ball milling for 1-3h to obtain powder C; 4) Activate powdered C at 600-1000°C under argon protective atmosphere, with a heating rate of 10-30°C / min, a gas flow rate of 60-100 sccm, a holding time of 1-5h, and cool to room temperature to obtain powdered D; 5) Adding hydrochloric acid solution to powder D, adding 1-5 g of powder D to every 40-90 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 1-5 mol / L, the water bath temperature is 70-90° C., stirring for 6-12 hours, the obtained product is washed with deionized water and ethanol, filtered, and dried in an oven at 70-90° C. for 24-48 hours to obtain powder E, that is, a biomass porous carbon material; 6) The biomass porous carbon material and sulfur powder (sublimed sulfur) are mixed in a mass ratio of 5:5, 4:6, 3:7 or 2:8, and maintained at 155-180° C. for 12-18 hours in a polytetrafluoroethylene liner to obtain a biomass porous carbon electrode material.
[0039] The present invention also discloses a biomass porous carbon electrode material prepared by the above-mentioned preparation method. Since the biomass porous carbon material has a multi-level pore structure, this structure can accommodate more sulfur and provide sufficient space to alleviate the volume expansion of sulfur during the charging and discharging process. Therefore, the prepared electrode material exhibits extremely high specific capacity and excellent cycle stability in a room temperature sodium-sulfur battery. The macropores, mesopores and small pores in the multi-level pore structure are interconnected to form an effective ion transport network. This structure is conducive to the rapid diffusion and migration of electrolyte ions, thereby reducing the internal resistance of the battery and improving the rate performance of the battery. The small pore structure of the biomass porous carbon material can provide a large specific surface area and adsorption volume, which is helpful to capture and fix polysulfides, thereby effectively inhibiting the shuttle effect of polysulfides in the electrolyte. This significantly improves the coulombic efficiency and cycle life of the battery. The use of biomass waste as raw materials not only reduces the cost of raw materials, but also reduces dependence on traditional fossil resources.
[0040] The present invention also discloses the application of the biomass porous carbon electrode material prepared by the above preparation method in a room temperature sodium-sulfur battery. The electrode material prepared by the present invention is applied to the room temperature sodium-sulfur battery, which not only exhibits excellent electrochemical performance, but also has good economic benefits and environmental friendliness. The application of the biomass porous carbon electrode material in the room temperature sodium-sulfur battery can increase the stability during the electrochemical reaction, thereby improving the rate performance of the battery system and ensuring the stability of long cycles at high current density.
[0041] The present invention is described in further detail below in conjunction with embodiments: Example 1 (Named as YMBA-600, and named as YMBA-600@S after mixing with sulfur powder) A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 70°C for 24 hours, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 600°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 4 hours, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:4. After mixing, the mixture is ball-milled for 2 hours to obtain powder C; 4) Activate powdered C at 800°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 5 h, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 1 g of powder D to every 90 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 3 mol / L, heat to 70°C and stir in a water bath for 6 h. The obtained product is washed with deionized water and ethanol, filtered, and dried in an oven at 70°C for 48 h to obtain powder E, that is, a biomass porous carbon material.
[0042] 6) The biomass porous carbon material and sulfur powder (sublimated sulfur) were mixed in a mass ratio of 4:6 and kept at 155°C for 12 hours in a polytetrafluoroethylene liner to obtain the biomass porous carbon electrode material YMBA-600@S.
[0043] Example 2 (Named as YMBA-800, and named as YMBA-800@S after mixing with sulfur powder) A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 70°C for 24 hours, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 800°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 4 hours, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:4. After mixing, the mixture is ball-milled for 2 hours to obtain powder C; 4) Activate powdered C at 800°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 5 h, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 1 g of powder D to every 90 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 3 mol / L, heat to 70°C and stir in a water bath for 6 h. The obtained product is washed with deionized water and ethanol, filtered, and dried in an oven at 70°C for 48 h to obtain powder E, that is, a biomass porous carbon material.
[0044] 6) The biomass porous carbon material and sulfur powder (sublimated sulfur) were mixed in a mass ratio of 4:6 and kept at 155°C for 12 h in a polytetrafluoroethylene liner to obtain the YMBA-800@S material.
[0045] Example 3 (Named as YMBA-1100, and named as YMBA-1100@S after mixing with sulfur powder) A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 70°C for 24 hours, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 1100°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 4 hours, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:4. After mixing, the mixture is ball-milled for 2 hours to obtain powder C; 4) Activate powdered C at 800°C under argon protective atmosphere, with a heating rate of 15°C / min, a gas flow rate of 90 sccm, a holding time of 5 h, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 1 g of powder D to every 90 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 3 mol / L, heat to 70°C and stir in a water bath for 6 h. The obtained product is washed with deionized water and ethanol, filtered, and dried in an oven at 70°C for 48 h to obtain powder E, that is, a biomass porous carbon material.
[0046] 6) The biomass porous carbon material and sulfur powder (sublimated sulfur) were mixed in a mass ratio of 4:6 and kept at 155°C for 12 h in a polytetrafluoroethylene liner to obtain the YMBA-1100@S material.
[0047] Figure 1 From the XRD diagrams of the biomass porous carbon electrode materials prepared in Examples 1, 2 and 3 of the present invention, it can be seen that as the pre-carbonization temperature increases, the amorphous peak shifts to the right, the interplanar spacing decreases, and the degree of graphitization increases. Among them, Example 1 has the largest interplanar spacing and the lowest degree of graphitization, providing a larger space for the deintercalation of sodium ions.
[0048] Figure 2These are SEM images of the biomass porous carbon electrode materials prepared in Example 1, Example 2, and Example 3 of the present invention; wherein, (a) is a 10,000-fold SEM image of Example 1; (b) is a 10,000-fold SEM image of Example 2; (c) is a 10,000-fold SEM image of Example 3; (d) is a 50,000-fold SEM image of Example 1; (e) is a 50,000-fold SEM image of Example 2; (f) is a 50,000-fold SEM image of Example 3; it can be seen that Example 1 has more pores, providing more embedding sites for sodium ions.
[0049] Figure 3 The Raman spectra of the biomass porous carbon electrode materials prepared in Examples 1, 2 and 3 of the present invention show that as the temperature increases, I D :I G The decrease in the value means that the disorder or defects are reduced and the degree of graphitization is increased, which is consistent with the XRD result. Among them, the value of Example 1 is the largest, the degree of graphitization is the lowest, and the disorder or defects are the most.
[0050] Figure 4 The biomass porous carbon electrode material prepared in Example 1 and Example 2 of the present invention is 5A g -1 The long cycle performance diagram under the condition of Fig. 2 shows that Example 1 has the highest absolute capacity and excellent stability, which can provide about 700 mAh g -1 The charge-discharge specific capacity.
[0051] Figure 5 The rate performance diagram of the biomass porous carbon electrode material prepared in Example 1, Example 2, and Example 3 of the present invention; among them, Example 1 has the highest absolute capacity and has a high capacity at 10A g -1 It can still maintain nearly 800mAh g at a high rate -1 The charge-discharge specific capacity.
[0052] Example 4 A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 75°C for 12 h, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 700°C under argon protective atmosphere, with a heating rate of 10°C / min, a gas flow rate of 60 sccm, and a holding time of 3 h, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:1. After mixing, the mixture is ball-milled for 1 hour to obtain powder C; 4) Activate powdered C at 600°C under argon protective atmosphere, with a heating rate of 10°C / min, a gas flow rate of 60 sccm, a holding time of 1 h, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 2 g of powder D to every 40 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 1 mol / L, heat to 75°C and stir in a water bath for 8 h. The obtained product is washed with deionized water and ethanol, filtered, and dried in an oven at 75°C for 24 h to obtain powder E, that is, a biomass porous carbon material.
[0053] 6) The biomass porous carbon material and sulfur powder (sublimed sulfur) were mixed in a mass ratio of 5:5 and kept at 160° C. for 18 h in a polytetrafluoroethylene liner to obtain a biomass porous carbon electrode material.
[0054] Example 5 A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 80°C for 18 h, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 900°C under argon protective atmosphere, with a heating rate of 20°C / min, a gas flow rate of 80 sccm, a holding time of 3.5 h, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:3. After mixing, the mixture is ball-milled for 1.5 hours to obtain powder C; 4) Activate powdered C at 900°C under argon atmosphere, with a heating rate of 20°C / min, a gas flow rate of 80 sccm, and a holding time of 3 h, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 3 g of powder D to every 60 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 2 mol / L, heat to 80 ° C in a water bath and stir for 10 h, wash the obtained product with deionized water and ethanol, filter it, and dry it in an oven at 80 ° C for 32 h to obtain powder E, that is, obtain biomass porous carbon material.
[0055] 6) The biomass porous carbon material and sulfur powder (sublimed sulfur) were mixed in a mass ratio of 3:7 and kept at 170° C. for 16 h in a polytetrafluoroethylene liner to obtain a biomass porous carbon electrode material.
[0056] Example 6 A method for preparing a biomass porous carbon electrode material comprises the following steps: 1) The corn stalks were cleaned with deionized water and ethanol in sequence, and then dried in an oven at 90°C for 20 h, and then crushed and ground to obtain powder A; 2) Pre-carbonize powder A at 1400°C under argon protective atmosphere, with a heating rate of 30°C / min, a gas flow rate of 100 sccm, a holding time of 5 h, and cool to room temperature to obtain powder B; 3) Add a pore-forming agent to powder B, wherein the pore-forming agent is potassium citrate, and the mass ratio of powder B to the pore-forming agent is 1:5. After mixing, the mixture is ball-milled for 3 hours to obtain powder C; 4) Activate powdered C at 1000°C under argon protective atmosphere, with a heating rate of 30°C / min, a gas flow rate of 100 sccm, a holding time of 4 hours, and cool to room temperature to obtain powdered D; 5) Add hydrochloric acid solution to powder D, add 5 g of powder D to every 80 mL of hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 5 mol / L, heat to 90 ° C and stir in a water bath for 12 h, wash the obtained product with deionized water and ethanol, filter it, and dry it in an oven at 90 ° C for 40 h to obtain powder E, that is, obtain biomass porous carbon material.
[0057] 6) The biomass porous carbon material and sulfur powder (sublimed sulfur) were mixed in a mass ratio of 2:8 and kept at 180° C. for 14 h in a polytetrafluoroethylene liner to obtain a biomass porous carbon electrode material.
[0058] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a biomass porous carbon electrode material, characterized in that: include: After pre-treatment of biomass waste, powder A is obtained; Pre-carbonizing powder A to obtain powder B; Add pore-forming agent to powder B and mix and ball-mill to obtain powder C; After activating powdered C, powdered D is obtained; hydrochloric acid solution is added to powdered D, heated and stirred, washed, filtered, and dried to obtain a biomass porous carbon material, and then the biomass porous carbon material is mixed with sulfur powder, and after heat treatment, a biomass porous carbon electrode material is obtained.
2. The method for preparing the biomass porous carbon electrode material according to claim 1, characterized in that: The biomass waste is corn stalks; the pretreatment conditions are: washing with deionized water and ethanol in sequence and drying and grinding; the drying conditions are drying at 70-90° C. for 12-24 hours.
3. The method for preparing the biomass porous carbon electrode material according to claim 1, characterized in that: The pre-carbonization conditions are: in an argon protective atmosphere, heating to 600-1400° C. at a heating rate of 10-30° C. / min, and keeping the temperature for 3-5 hours; the argon flow rate is 60-100 sccm.
4. The method for preparing a biomass porous carbon electrode material according to claim 1, characterized in that: The pore-forming agent is potassium hydroxide, potassium citrate, zinc chloride or sodium hydroxide; the mass ratio of the powder B to the pore-forming agent is 1:(1-5); and the ball milling time is 1-3h.
5. The method for preparing the biomass porous carbon electrode material according to claim 1, characterized in that: The activation conditions are: in an argon protective atmosphere, heating to 600-1000° C. at a heating rate of 10-30° C. / min, and keeping the temperature for 1-5 hours; the argon gas flow rate is 60-100 sccm.
6. The method for preparing a biomass porous carbon electrode material according to claim 1, characterized in that: For every 1-5 g of the powdered D, 40-90 mL of a hydrochloric acid solution having a concentration of 1-5 mol / L is added.
7. The method for preparing a biomass porous carbon electrode material according to claim 1, characterized in that: The heating and stirring conditions are: heating and stirring at a speed of 300 r / min in a 70-90° C. water bath for 6-12 hours; the cleaning conditions are: cleaning with deionized water and ethanol in sequence; and the drying conditions are: drying at 70-90° C. for 24-48 hours.
8. The method for preparing a biomass porous carbon electrode material according to claim 1, characterized in that: The mass ratio of the biomass porous carbon material to the sulfur powder is (2-5): (5-8); the heat treatment conditions are: heat treatment at 155-180° C. for 12-18 hours.
9. A biomass porous carbon electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the biomass porous carbon electrode material prepared by the preparation method according to any one of claims 1 to 8 in room temperature sodium-sulfur batteries.
Citation Information
Patent Citations
Corn straw based biological carbon / sulfur composite material as well as preparation method and application thereof
CN104681800A
Preparation method and application of biomass-based porous carbon / sulfur composite
CN106981644A
Cited By
Method for preparing nano hydrothermal carbon sphere-transition metal hydroxide composite material through in-situ growth
CN121035207A